GLOBAL RESEARCH TREND ON POLITICAL EDUCATION FOR STUDENTS IN UNIVERSITY: A BIBLIOMETRICS ANALYSIS - Dimas Subekti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to explain the research development on Political Education for Students at University. This study uses the scoping review method. The finding of this study is that research publications with this theme have yet to develop significantly over the past ten years. This is indicated by each year the publication has a very static trend in terms of number. This finding is a concern that the theme of this matter is outside the lyrics or interest of scientists or researchers, even though the benefits are significant for young people, especially university students. Then, the United States and the United Kingdom contributed the most to developing this theme, b terms of countries and affiliations contained therein. Furthermore, the key takeaways from the theme of this research publication are that Students in higher education (HE) are frequently seen as significant political players in the larger society, an expectation that students should be politically active. To ensure that young people participate in and have an impact on democratic politics, a vital component of this education in democratic nations is teaching them to comprehend and engage in democratic processes.